Pengaruh Budaya Organisasi, Iklim Kerja, dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan (pada Karyawan di Rumah Makan Padang Payakumbuah Veteran Bintaro): Pada Karyawan di Rumah Makan Padang Payakumbuah Veteran Bintaro - Maisun Naziah; Qodariah Qodariah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the influence of Organizational Culture (X1), Work Climate (X2), and Work Discipline (X3) on Employee Job Satisfaction (Y) at a company with 52 employees as respondents. The sampling technique used was non-probability sampling with a saturated sample method, meaning all members of the population were included in the sample. Data were collected using a structured questionnaire based on a Likert scale and then analyzed using SPSS version 25. The research employed a quantitative approach with multiple linear regression analysis to examine the relationships between the variables. The results showed that both organizational culture and work discipline had a significant and positive effect on employee job satisfaction. A strong organizational culture contributes to a shared vision, values, and sense of belonging, which enhances job satisfaction. Work discipline, on the other hand, ensures employees meet performance expectations and follow organizational rules, which promotes a stable and productive work environment. Although the work climate variable did not show as strong an influence as the other two, it still plays an important role in shaping employee perceptions and comfort in the workplace. Overall, the findings suggest that improving organizational culture and reinforcing work discipline are effective strategies for enhancing employee job satisfaction, while maintaining a supportive work climate can further support this effort.